Dam risk management framework on the lifecycle of dam: A comparative analysis in a legislation perspective - Mayangsari, Anissa; Sutjiningsih, Dwita; Irianto, Eko Winar; Karuniasa, Mahawan (International Journal of Innovative Research and Scientific Studies, 2025)
Dams play essential roles in water management and produce renewable energy but pose high potential risks, not only for communities downstream of the dam but also for economic and environmental damage. Risk management is an effort to reduce dam risks by knowing the measurable risk factors in a dam. Several countries have adopted risk management as one of the cycles in ensuring dam safety and include it in applicable regulations and guidelines. Using the comparative analysis method, this paper will compare risk management regarding regulations and guidelines in the context of dam safety in various countries such as New Zealand, India, Spain, and Indonesia. These results show that dam hazard classification is the primary basis for determining design, construction, operation, and maintenance criteria, such as design flood design and earthquake analysis. All of the countries stated that risk management is mandatory in the lifecycle of the dam, but only Indonesia still makes it voluntary. Guidelines on risk analysis have been prepared in each country to explain the legislation and regulations that have been established. Considering the current conditions where society demands transparency in decision-making, dam risk assessment as a method to assess risk-based information is essential, and regulations related to risk management should be made mandatory in the lifecycle of dams.